Integration of Palembang Cultural Products in the Learning of Electrolyte and Nonelectrolyte Solutions: An Ethnopedagogical Approach - Mario Aditya Prasetyo; Yuli Rahmawati; Yussi Pratiwi (Universitas Lampung, 2021)
Meaningful chemistry learning can occur if students can connect new knowledge with previously owned knowledge. It is challenging for teachers to carry out a meaningful learning process by linking different students' cultural backgrounds and characters. This study used an ethnopedagogical approach in studying electrolyte and nonelectrolyte solution materials using Palembang cultural products that contain chemical aspects, namely (1) cuko (gravy) pempek contains vinegar which is a weak electrolyte solution, (2) kuah (sauce) pindang contains citric and tartaric acids, which are weak electrolytes, and (3) in the process of making Batik Palembang using caustic soda for coloring which is an example of a strong electrolyte. This research aimed to develop creative and meaningful learning methods to improve the quality of learning. This research was conducted in class X IPA 1 SMA Negeri 5 Palembang in January-March 2021. Qualitative descriptive methods and ethnopedagogical approaches were used in this research. It was carried out through five stages, namely Self Identification by conducting interviews to determine cultural background, Content Integration by providing ethnochemical articles, Collaboration by doing practicum, Dialogue by conducting discussions, and Reflection by filling in reflective journals. Based on this research, it can be seen that students can connect chemical concepts with local wisdom through cultural products. Students do not find it challenging to understand electrolyte and nonelectrolyte solution material because they use cultural products closely related to everyday life.